An Analysis of Marketing Strategy of JP. Astor Products in PT. Jasaraharja Putera of Bengkulu City - Wahyu Ilahi; Karona Cahya Susena; Eska Prima Monique Damarsiwi (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the marketing strategy of JP ASTOR products in PT. Jasaraharja Putera. This research is qualitative and quantitative research. The sample in this study is an internal sample, that is from employees of PT. Jasaraharja Putera and external samples are from customers of PT. Jasaraharja Putera. The analytical method used is the EFAS analysis method (External Factor Analysis Summary) and IFAS (Internal Factor Analysis Summary) then included in the matrix Strength, Weakness, Opportunities and Threats, or SWOT. Based on the results of the research,it is found that PT. Jasaraharja Putera gained score of 9.17 on internal factors and score of 3.51 on external factors. Thus scores make the company is in quadrant 1 in the SWOT analysis diagram (Supporting Aggressive strategies) which means that the company uses the power possessed by the company itself in marketing JP. ASTOR products.